(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
This article presents a proposal to the high rates of dropout and repetition of the careers that contemplate in his curriculum the basic sciences, in the same way as the four blocks of this career. The level of knowledge in the basic sciences is determinant for the success and permanence of the student in the industrial engineering career. The reason why it is established as a measure to determine this level of knowledge, the tests of diagnostic location, are elaborated through a systematic and rigorous process. If the student does not pass these tests, have the option to take the level. With that’s proposal hopes to guarantee the success and the permanence of the students in the race of industrial engineering.